PENATAAN KEMBALI DESAIN KELEMBAGAAN KOMISI NASIONAL DISABILITAS SEBAGAI LEMBAGA INDEPENDEN DI INDONESIA - Rayhan Naufaldi Hidayat; Andradito Muhammad Wisnu (Al-Adl : Jurnal Hukum, 2021)
Indonesia is working hard to create a country that is friendly for people with disabilities. One of the concrete efforts that have been made is to form an independent agency that specifically handles the disability sector. The agency is in the form of a commission on behalf of the National Commission for Disabilities. Its formation is based on Presidential Regulation Number 68 of 2020 concerning the National Commission for Disabilities. In this regard, this study will examine further the institutional design of the commission from the point of view of state institutional law. The type of research used in this research is normative legal research with a statutory approach. The results of this study indicate that there are still serious legal problems related to the institutional design of the National Commission for Disabilities as an independent agency. This can be seen in Article 9 of Presidential Regulation Number 68 of 2020 concerning the National Commission for Disabilities which embeds the secretariat of the commission within the Ministry of Social Affairs, so that directly or indirectly the implementation and supervision functions of the National Commission for Disabilities are not optimal. The implication that arises from this condition is the rise of cases of violations of the rights of persons with disabilities. Therefore, it is necessary to restructure the institutional design of the National Commission for Disabilities as an independent agency so that it can carry out its duties, principals and functions optimally, so that Indonesia's efforts to create a disability-friendly country can actually be realized.